The collaborated assembly of hydrophobic curcumin and hydrophilic cyanine dye into nanocolloid for synergistic chemo-photothermal cancer therapy - Meichen Zheng; Jingjing Zhang; Caiting Deng; Lei Chen; Heng Zhang; Jingqi Xin; Omer Aras; Mengjiao Zhou; Feifei An; Yu Ren (Materials & Design, 2024)
Carrier-free nanomedicine represents a new opportunity of using less inert materials for efficient drug delivery. To date, most reported carrier-free nanomedicine systems rely heavily on π-π stacking interaction between hydrophobic drugs. This work found that the hydrophilic IR783 dye can collaborate with the hydrophobic curcumin (Cur) compound to form a novel Cur@IR783 nanocolloid (NC) via self-assembly. The self-assembly of the hydrophilic IR783 and hydrophobic Cur improved the water dispersity of Cur, significantly facilitating its administration in vivo. Moreover, Cur@IR783 NC retained the IR783 properties of NIR fluorescence and photothermal conversion efficiency. Fluorescence imaging demonstrated that Cur@IR783 NC accumulated at the tumor site via the enhanced permeation and retention effect, which ensured enhanced anti-tumor effect. In vitro and in vivo experiments showed that the Cur@IR783 NC with laser irradiation yielded the most potent antitumor effect, and Cur@IR783 NC exhibited high biocompatibility. Overall, Cur@IR783 NC showed remarkable synergistic antitumor activity via chemo-photothermal combination therapy, providing a new promising approach for Cur-based applications in cancer treatment.